Late nineteenth-century globalization: London and Lomagundi perspectives on mining speculation in southern Africa, 1894–1904. Issue 1 (18th February 2015) - Phimister, Ian
Abstract: In southern Africa the portal of globalization opened by finance capital towards the end of the nineteenth century frequently turned on mining speculation. A particularly notorious case was that of the Ayrshire mine in Southern Rhodesia's Lomagundi district. Touted in its heyday as the richest gold prospect in the entire southern half of the continent, the Ayrshire's corporate existence was characterized by company-mongering and market manipulation in the City of London. Few of these concerns immediately impinged on indigenous interests. As interaction between the global and the local was sporadic and contingent, local politics of dynastic accommodation only gradually gave way to global dynamics of dispossession and accumulation.